(untitled) (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2022)
Of the great chapters of Christian theology, anthropology is the most challenged—and challenging—component of this thought. Paradoxically, the interest of the postmodern individual for their existence is increasingly evident. At least two of the predominant existentialist values are at the forefront: the freedom and human dignity. The paper analysis the point of view of secular contemporary anthropology in parallel with the true teaching on human being and its position in society, as the Saviour Jesus Christ, the God-Man, saw and applied it through his own incarnation, death and resurrection. These divine acts, integrated in the liturgical life of the church, can fix the shortcomings and incoherence of a secular anthropology that isolates more and more the contemporary individual from God and his fellow human beings.